Human factors in management - Hoslett, Schuyler Dean. (New York : Harper, 1951)
The book is organized around the major problem areas in human relation as seen from both a managerial and an academic point of view.
Includes bibliographical p.325-327.
hza 13/07/2018
Loans
Keywords: Personnel management